Medical Management of ST elevation Myocardial infarction - Where are we? - Adhikari, Chandra Mani; Rajbhandari, Sujeeb; Prajapati, Dipanker; Shrestha, Nagma; Baniya, Bibeka; Bogati, Amrit; Gurung, Prakash; Thapaliya, Suman (Nepalese Heart Journal, 2014)
Background and Aims: Despite well developed guidelines in the management of ST elevation myocardial infarction, registries worldwide have demonstrated incomplete implementation of evidence-based recommendations. Our study aims to assess the adherence of our practices to the recommended clinical guidelines, which is based on the discharge prescription in Shahid Gangalal National Heart Centre. Methods: Medical records of 495 ST elevation myocardial infarction patients discharged from our centre in between January 2012 to December 2012 were retrospectively reviewed. Results: Among the 495 patients included in this study, 372 (75.1%) were males and 123 (24.9%) were females. The mean age was 56.9±12.4 years. Aspirin, Clopidrogel and statin were prescribed in more than 95% of the patients. Angiotensin Converting Enzyme inhibitor/ Angiotensin Receptor blockers was prescribed more often than β-blockers. Only a small numbers of patients were discharged without Angiotensin Converting Enzyme inhibitor /Angiotensin Receptor Blockers or β-blockers. Conclusions: Usage of Aspirin, clopidogrel, statins, beta blockers and Angiotensin Converting Enzyme inhibitor/ Angiotensin Receptor Blockers s is comparable to international studies. We still need some effort to increase improve our prescription rate of β-blockers and Angiotensin Converting Enzyme inhibitor/ Angiotensin Receptor Blockers. DOI: http://dx.doi.org/10.3126/njh.v11i1.10981 Nepalese Heart Journal 2014;11(1): 45-48